Healthcare workers' SARS-CoV-2 infection rates during the second wave of the pandemic: follow-up study - Anne Mette Würtz; Martin B Kinnerup; Kirsten Pugdahl; Vivi Schlünssen; Jesper Medom Vestergaard; Kent Nielsen; Christine Cramer; Jens Peter Bonde; Karin Biering; Ole Carstensen; Karoline Kærgaard Hansen; Annett Dalbøge; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: This study aimed to assess if, during the second wave of the COVID-19 pandemic, healthcare workers had increased severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection rates, following close contact with patients, co-workers and persons outside work with COVID-19. METHODS: A follow-up study of 5985 healthcare workers from Denmark was conducted between November 2020 and April 2021 and provided day-to-day information on COVID-19 contacts. SARS-CoV-2 infection was defined by the first positive polymerase chain reaction (PCR) test ever. Data was analyzed in multivariable Poisson regression models. RESULTS: The SARS-CoV-2 infection rates following close contact 3-7 days earlier with patients, co-workers and persons outside work with COVID-19 were 153.7, 240.8, and 728.1 per 100 000 person-days, respectively. This corresponded with age, sex, month, number of PCR tests and mutually adjusted incidence rate ratios of 3.17 [40 cases, 95% confidence interval (CI) 2.15-4.66], 2.54 (10 cases, 95% CI 1.30-4.96) and 17.79 (35 cases, 95% CI 12.05-26.28). The risk of SARS-CoV-2 infection was thus lower, but the absolute numbers affected was higher following COVID-19 contact at work than COVID-19 contact off work. CONCLUSIONS: Despite strong focus on preventive measures during the second wave of the pandemic, healthcare workers were still at increased risk of SARS-CoV-2 infection when in close contact with patients or co-workers with COVID-19. There is a need for increased focus on infection control measures in order to secure healthcare workers' health and reduce transmission into the community during ongoing and future waves of SARS-CoV-2 and other infections.